Investigating Computer Screen and Paper Reading Speed Differences - Kurniawan, Sri Hastuti; Zaphiris, Panayiotis (My University, 2001)
This paper presents the results of an experiment measuring the difference of reading speed and preference when reading on paper or screen. Extending previous experiments on the topic of reading speed measurements, which usually concentrate in specific age groups, in this experiment, forty two participants from across the adult life span took part in reading on computer screen or on paper. Results are in agreement with previous studies, which showed that reading from paper is significantly faster (around 10-30%) than reading from screen. No significant differences in terms of speed and preference among the three information layouts (one-column, two column and three-column formats) used in this experiment were found.